The Effect of Good Corporate Governance on Financial Reporting Quality of BEI Listed Banking Companies - Ramadhan, Rachmad; Kusumaningtias, Rohmawati (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Good Corporate Governance (GCG) reflects a company's commitment to transparency, accountability, and integrity in achieving corporate goals. The implementation of GCG mechanisms such as audit committees, independent commissioners, and boards of commissioners plays an important role in building stakeholder trust and ensuring the credibility of financial reporting. In recent years, GCG has gained attention as a major factor influencing the quality of financial reporting and controlling earnings management practices. This study aims to examine the effect of GCG on the quality of financial reporting in Indonesian banking companies, emphasizing its role in improving corporate accountability and performance. The method used is a systematic literature review by examining various previous studies on the effectiveness of GCG mechanisms in improving financial reporting transparency. The results show that the independence of the board of commissioners has a positive effect in suppressing earnings management, while the audit committee and board of commissioners often show limited or inconsistent effects. Overall, the effectiveness of GCG is highly dependent on the competence, independence, and active involvement of governance bodies, so strengthening the implementation of GCG is necessary to improve the credibility of financial reports and stakeholder trust